REMEDIASI MISKONSEPSI SISWA MELALUI PEMBELAJARAN LANGSUNG DISERTAI PETA KONSEP PADA MATERI PERHITUNGAN KIMIA KELAS X SMA NEGERI 1 SEKAYAM - Kristiawan, Wisnu; Hairida, Hairida; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The aim of this research was to: 1) Determine there was misconception of students in 10th grade SMA Negeri 1 Sekayam in chemistry calculation concepts; 2) Determine Direct Instruction with concept mapping whether can minimize misconception of students in X science class SMA Negeri 1 Sekayam in chemistry calculation. A research form is experimental research with research subjects thirty three peoples. Test and instrument used to collect the data are diagnostic test and learning tools (RPP, LKS and concept mapping). Diagnostic test formed multiple choice that consisting of twenty question with certeainty of response index. Validation used is validation of content, and reability used is KR-20 with the result 0,492. The result of this research show students be through misconception in pretest amount of 21,56% and in posttest amount of 27,74%. Direct Instruction with concept mapping haven’t been able to minimize misconception of students in 10th grade SMA Negeri 1 Sekayam by overall in chemistry calculation, based on resulf of statistic test with SPSS, be obtained score of Sig. (2-tailed) amount of 0,002. Because score of Sig (2-tailed) 0,002<0,05, thus can be concluded that Ho unacceptable. Keyword : misconception, certainty of response index, concept mapping, minimize